GIMAP7 as a Potential Predictive Marker for Pan-Cancer Prognosis and Immunotherapy Efficacy - Qin Y; Liu H; Huang X; Huang L; Liao L; Li J; Zhang L; Li W; Yang J (Dove Medical Press, 2022)
Yan Qin,1,* He Liu,1,* Xiaoliang Huang,2 Lihaoyun Huang,2 Lixian Liao,2 Jiasheng Li,2 Lihua Zhang,2 Wei Li,1 Jianrong Yang1 1Department of Health Management, The People's Hospital of Guangxi Zhuang Autonomous Region & Research Center of Health Management, Guangxi Academy of Medical Sciences, Nanning, Guangxi, 530021, People's Republic of China; 2Guangxi Medical University Cancer Hospital, Nanning, Guangxi, 530021, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianrong Yang; Wei Li, Health Examination Center, The People's Hospital of Guangxi Zhuang Autonomous Region, Email gandansurgery2014@163.com; lw6666gx@aliyun.comBackground: GIMAP, a GTP enzyme of immune-related proteins, plays a crucial role in immune mechanisms. Investigating GIMAP7 expression in pan-cancer can provide efficient guidance for predicting clinical prognosis and identifying novel immunotherapy targets.Methods: Gene expression in different tumour types and stages was analysed based on The Cancer Genome Atlas and the Genotype-Tissue Expression database. An immunohistochemical assay was used to explore the differences in GIMAP7 protein levels in different tumour types and stages. Further, the cBioPortal was used to obtain the genetic variation characteristics of GIMAP7. Kaplan-Meier analysis and multivariable Cox regression analysis were performed to assess the prognostic value of GIMAP7. The pathways affected by GIMAP7 were studied based on gene set enrichment analysis, and the correlation between GIMAP7 expression and immune infiltration was determined using the TIMER2 database and the CIBERSORT method. ESTIMATE was used to analyse the correlation between GIMAP7 expression and ESTIMATE, immune and stromal scores. In addition, the correlation between GIMAP7 and immunoregulators was analysed. Furthermore, tumour mutational burden and microsatellite instability were evaluated using Spearman correlation assay.Results: GIMAP7 expression was significantly low and predicted better survival status in most tumour types. GIMAP7 was positively correlated with the abundance of CD8 + and CD4 + T cells in the tumour microenvironment. However, the high expression of GIMAP7 was negatively correlated with tumour mutations in uveal melanoma and colon adenocarcinoma. A correlation between GIMAP7 and microsatellite instability was found in rectal adenocarcinoma. Additionally, GIMAP7 presented a robust correlation between immune modulators and immunotherapeutic markers. Moreover, high GIMAP7 expression was significantly related to immune-relevant pathways.Conclusion: This study suggests the potential role of GIMAP7 as a prognostic and immunotherapeutic marker in pan-cancer, laying the groundwork for prospective functional and mechanistic experiments and their impact in the clinical setting.Keywords: immune-associated nucleotide-binding protein 7, pan-cancer analysis, immunoregulation, immunotherapy, CD8-positive T cells